Visible‐Light Removable Photocaging Groups Accepted by MjMAT Variant: Structural Basis and Compatibility with DNA and RNA Methyltransferases. (25th October 2021) - Peters, Aileen; Herrmann, Eric; Cornelissen, Nicolas V.; Klöcker, Nils; Kümmel, Daniel; Rentmeister, Andrea
Abstract: Methylation and demethylation of DNA, RNA and proteins constitutes a major regulatory mechanism in epigenetic processes. Investigations would benefit from the ability to install photo‐cleavable groups at methyltransferase target sites that block interactions with reader proteins until removed by non‐damaging light in the visible spectrum. Engineered methionine adenosyltransferases (MATs) have been exploited in cascade reactions with methyltransferases (MTases) to modify biomolecules with non‐natural groups, including first evidence for accepting photo‐cleavable groups. We show that an engineered MAT from Methanocaldococcus jannaschii (PC‐MjMAT) is 308‐fold more efficient at converting ortho ‐nitrobenzyl‐(ONB)‐homocysteine than the wildtype enzyme. PC‐MjMAT is active over a broad range of temperatures and compatible with MTases from mesophilic organisms. We solved the crystal structures of wildtype and PC‐MjMAT in complex with AdoONB and a red‐shifted derivative thereof. These structures reveal that aromatic stacking interactions within the ligands are key to accommodating the photocaging groups in PC‐MjMAT. The enlargement of the binding pocket eliminates steric clashes to enable AdoMet analogue binding. Importantly, PC‐MjMAT exhibits remarkable activity on methionine analogues with red‐shifted ONB‐derivatives enabling photo‐deprotection of modified DNA by visible light. Abstract : An engineered MAT (methionine adenosyltransferase) exhibits remarkable activity on methionine analogues with red‐shifted ortho ‐nitrobenzyl (ONB)‐derivatives and is compatible with methyltransferases from thermophilic and mesophilic organisms. This enables photo‐deprotection of modified DNA by visible light. The crystal structure reveals details about substrate accommodation.